Exploring the relationship between students’ note-taking and interpreting quality: a case study in the Chinese context - Liu, Yuqiao; Luo, Weihua; Wang, Xiaochen (Frontiers in Education, 2023)
This paper aims to explore the relationship between note-taking and interpreting quality in consecutive interpreting. Research questions focus on three perspectives: language choice, the use of symbols and their influence on interpreting quality, and the problems in note-taking. The research design is divided into three steps: pre-interpretation preparation, consecutive interpretation, and retrospective interview. Through the empirical study, a mixed research method is adopted with the analysis of the notes and retrospective interviews with six participants whose major is translation and interpreting at a university in Northeast China. Specifically, both descriptive data analysis and correlation analysis are used for quantitative data, and thematic analysis aims to better describe qualitative data. Findings are as follows: first, students prefer to use English to take notes in English-to-Chinese consecutive interpreting, while Chinese is used more in Chinese-to-English consecutive interpreting; second, the number of symbols used is not related to the quality of interpreting; third, the following five problems are identified from the interview with student participants in students’ notes: missing key information, inconsistent abbreviations, unclear logics, incomplete records of figures and the meaning of figures, and inadequate records of high-density information. The identification of language choice and problems of note-taking in interpreting practice might help teachers and students understand the problems of students’ note-taking and shed light on teaching and learning consecutive interpreting.